2019
DOI: 10.1093/cid/ciz139
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Effects of 10-Valent Pneumococcal Conjugate Vaccine Against Adult Pneumococcal Pneumonia in Rural Western Kenya

Abstract: Background: Data on pneumococcal conjugate vaccine (PCV) indirect effects in low-income countries with high HIV burden are limited. We examined adult pneumococcal pneumonia incidence before and after 10-valent PCV introduction in Kenya in 2011. Methods: From 1/1/2008 to 12/31/2016, we conducted surveillance for acute respiratory infection (ARI) among ~12,000 adults (≥18 years) in western Kenya, where HIV prevalence ~17%. ARI cases (cough or difficulty breathing or chest pain, plus temperature ≥38.0◦C or oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Although ART has reduced the risk of IPD and subsequent mortality [ 3 , 40 ], the risk remains more than 30-fold higher than in HIV-uninfected adults [ 41 ] with an incidence of >50 cases per 100,000 person years [ 3 , 5 , 42 ]. The introduction of infant PCV programs in South Africa and Kenya has led to a further reduction in VT-IPD and pneumococcal pneumonia incidence in HIV-infected adults [ 9 , 43 , 44 ].…”
Section: Pneumococcal Burden In African Hiv-infected Adultsmentioning
confidence: 99%
“…Although ART has reduced the risk of IPD and subsequent mortality [ 3 , 40 ], the risk remains more than 30-fold higher than in HIV-uninfected adults [ 41 ] with an incidence of >50 cases per 100,000 person years [ 3 , 5 , 42 ]. The introduction of infant PCV programs in South Africa and Kenya has led to a further reduction in VT-IPD and pneumococcal pneumonia incidence in HIV-infected adults [ 9 , 43 , 44 ].…”
Section: Pneumococcal Burden In African Hiv-infected Adultsmentioning
confidence: 99%
“…Previous studies have shown increases over time in the indirect effect of childhood vaccination with PCV7 and PCV13 on adult invasive pneumococcal disease [54] and pneumonia [15]. Indirect impact is not only related to time since vaccine introduction, but it is also affected by other factors such as vaccine coverage and timing.…”
Section: Discussionmentioning
confidence: 98%
“…For example, there is more frequent pneumococcal carriage in low-and middle-income countries with horizontal transmission between children and adults; developing country PCV schedules often do not include a post infancy booster dose (which may be critical to reductions in transmission) [10]; crowding and other factors may influence carriage density [11,12]; indoor and outdoor pollution may damage upper airway mucosa [13] which may also then influence pneumococcal carriage; and transmission pathways may differ by geography such as the potential for serotype 1 transmission outside of early childhood in the African meningitis belt [14]. One of the few studies in a resource poor setting [15] from Kenyareported a 47 to 94% reduction in adult pneumococcal pneumonia incidence following the introduction of the 10-valent PCV using a 3 + 0 schedule (6,10 and 14 weeks) in the childhood immunisation programme. Even though other improvements in healthcare may have contributed to the decline, the authors argued that the indirect PCV effect could have a considerable effect on adult disease in a high burden setting [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The PCV7 vaccine had caused a “replacement phenomena” in the serotypes causing disease. 4,5 Non-PCV7 serotype 19A became a major cause of severe AOM with high complication rates of mastoiditis, subperiosteal abscesses, and mastoidectomies due to its increased virulence and antibiotic resistance. 6,7 Due to the replacement phenomenon, as well as the severity of serotype 19A infection, PCV13 was released in 2010 with additional serotypes, including 19A.…”
Section: Introductionmentioning
confidence: 99%